6x-91=3x-10

Simple and best practice solution for 6x-91=3x-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-91=3x-10 equation:


Simplifying
6x + -91 = 3x + -10

Reorder the terms:
-91 + 6x = 3x + -10

Reorder the terms:
-91 + 6x = -10 + 3x

Solving
-91 + 6x = -10 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-91 + 6x + -3x = -10 + 3x + -3x

Combine like terms: 6x + -3x = 3x
-91 + 3x = -10 + 3x + -3x

Combine like terms: 3x + -3x = 0
-91 + 3x = -10 + 0
-91 + 3x = -10

Add '91' to each side of the equation.
-91 + 91 + 3x = -10 + 91

Combine like terms: -91 + 91 = 0
0 + 3x = -10 + 91
3x = -10 + 91

Combine like terms: -10 + 91 = 81
3x = 81

Divide each side by '3'.
x = 27

Simplifying
x = 27

See similar equations:

| 214-2x=34x+18 | | 9-6z=27 | | 4g+3(-7+2g)=1-g | | 14-7x=174-42x | | 2g+4(-6+2g)=1-g | | 36x=x*(r*r) | | 6x-91=3x-2 | | t^2-2t-36=0 | | -6g-4=-3g+2 | | 3x-4=4x-2 | | 3x-4=4x-ray | | -8=-2a+6 | | x^3-7x= | | 3x+29=11x-43 | | -6m+69-9(m-1)=4m-(2m-2)-7m+6 | | 10y^2-19y+6=0 | | 6p-8=8-30p | | 93=9*(e^2x) | | 2x+8=64-4x | | -3r+7=5r-3 | | 5.2y+7.2=30.6-1.3y | | 4b-21=28 | | y=4-3*2 | | 104-7x=29x+24 | | 0.47x=-3.23x+62.9 | | 93=9e^2x | | 7=9x-1 | | c+0.1c+0.01c-0.001c=c+0.545 | | 36-6x=18+3x | | n^2+n-400=0 | | 3(r-3)-r=-4(2r+5)-8 | | 3(s+4)+2s=67 |

Equations solver categories